Identification of the Role of Wnt/β-Catenin Pathway Through Integrated Analyses and in vivo Experiments in Vitiligo - Zhao SJ; Jia H; Xu XL; Bu WB; Zhang Q; Chen X; Ji J; Sun JF (Dove Medical Press, 2021)
Si-Jia Zhao,1 Hong Jia,2 Xiu-Lian Xu,1 Wen-Bo Bu,3 Qian Zhang,3 Xi Chen,4 Juan Ji,2 Jian-Fang Sun1 1Department of Pathology, Institute of Dermatology, Chinese Academy of Medical Sciences and Peking Union Medical College, Nanjing, Jiangsu, People’s Republic of China; 2Department of Dermatology, Institute of Dermatology, Chinese Academy of Medical Sciences and Peking Union Medical College, Nanjing, Jiangsu, People’s Republic of China; 3Department of Dermatologic Surgery, Institute of Dermatology, Chinese Academy of Medical Sciences and Peking Union Medical College, Nanjing, Jiangsu, People’s Republic of China; 4Department of Medicine 3, Universitätsklinikum Erlangen, Friedrich Alexander University Erlangen Nuremberg, Erlangen, Bavaria, GermanyCorrespondence: Jian-Fang SunInstitute of Dermatology, Chinese Academy of Medical Sciences and Peking Union Medical College, Nanjing, 210042, People’s Republic of ChinaTel +86 25 8547 8015Fax +86 25 8541 4477Email JianfangSunPUMC@outlook.comPurpose: Vitiligo is an acquired depigmentation skin disease, which affects an average of 1% of the world’s population. The purpose of this study is to identify the key genes and pathways responsible for vitiligo and find new therapeutic targets.Methods: The datasets GSE65127, GSE53146, and GSE75819 were downloaded from the Gene Expression Omnibus (GEO) database. R language was used to identify the differentially expressed genes (DEGs) between lesional skin of vitiligo and non-lesional skin. Next, the key pathways were obtained by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses. The protein–protein interaction (PPI) networks were conducted by STRING database and Cytoscape software. Subsequently, module analysis was performed by Cytoscape. Among these results, the Wnt/β-catenin pathway and melanogenesis pathway caught our attention. The expression level of β-catenin, microphthalmia-associated transcription factor (MITF) and tyrosinase (TYR) was detected by immunofluorescence in vitiligo lesions and healthy skin. Moreover, zebrafish was treated with XAV-939, an inhibitor of the Wnt/β-catenin pathway. After that, the area of melanin granules as a percentage of the head area was measured. The mRNA expression of β-catenin, lymphoid-enhancing factor 1(lef1), tyr and mitf were detected by q-PCR (quantitative polymerase chain reaction) in zebrafish (Danio rerio).Results: A total of 2442 DEGs were identified, including 1068 upregulated and 1374 downregulated DEGs. The key pathways were identified by GO and KEGG analyses, such as “NOD-like receptor signaling pathway”, “Wnt signaling pathway”, “Melanogenesis”, “mTOR signaling pathway”, “PI3K-Akt signaling pathway”, “Calcium signaling pathway” and “Rap1 signaling pathway”. The immunofluorescence results showed that the level of β-catenin, MITF and TYR was significantly downregulated in vitiligo lesional skin. In zebrafish, the mean percentage area of melanin granules and the expression of β-catenin, lef1, tyr and mitf were decreased after treated with XAV-939.Conclusion: The present study identified key genes and signaling pathways associated with the pathophysiology of vitiligo. Among them, the Wnt/β-catenin pathway played an essential role in pigmentation and could be a breakthrough point in vitiligo treatment.Keywords: vitiligo, zebrafish, melanogenesis, Wnt/β-catenin, calcium signaling, Rap1